Photodegradation of rhodamine B by Ag3PO4/Bi2MoO6nanocomposites under visible light illumination - Sudarat Sitthichai (2018)
© 2017 The Ceramic Society of Japan. All rights reserved. Heterostructure Ag 3 PO 4 /Bi 2 MoO 6 nanocomposites were synthesized by a depositionprecipitation method at high temperature and pressure. The as-synthesized products were characterized by X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. In this research, cubic Ag 3 PO 4 nanoparticles were deposited on orthorhombic Bi 2 MoO 6 nanoplates. For 10.0 wt% Ag 3 PO 4 loading, the Ag 3 PO 4 nanoparticles with 510nm in size were detected across the surface of Bi 2 MoO 6 nanoplates. The effect of Ag 3 PO 4 content on the photocatalytic properties was investigated by evaluating the degradation of rhodamine B under visible white light. The Ag 3 PO 4 /Bi 2 MoO 6 nanocomposites exhibited more enhanced photocatalytic activity than the pure Bi2MoO6. Electronhole diffusion in Ag 3 PO 4 /Bi 2 MoO 6 nanocomposites and photodegradation mechanism of rhodamine B were also discussed in this report.